2019
DOI: 10.53386/nilq.v70i1.237
|View full text |Cite
|
Sign up to set email alerts
|

Case review: Extraterritorial corporate liability for environmental harm: Okpabi v Royal Dutch Shell

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…After the analysis of five factors taken into account to determine the relation of proximity [89], it was concluded that there was no sufficient degree of control of operations of the Shell Petroleum Development Company of Nigeria Ltd. by Royal Dutch Shell to build the required degree of proximity [88]. A duty of care does not merely arise because of health and safety guidelines introduced by the parent company, which should apply to all subsidiaries [90].…”
Section: Typical Business Scenarios With the Participation Of Mnes: A...mentioning
confidence: 99%
“…After the analysis of five factors taken into account to determine the relation of proximity [89], it was concluded that there was no sufficient degree of control of operations of the Shell Petroleum Development Company of Nigeria Ltd. by Royal Dutch Shell to build the required degree of proximity [88]. A duty of care does not merely arise because of health and safety guidelines introduced by the parent company, which should apply to all subsidiaries [90].…”
Section: Typical Business Scenarios With the Participation Of Mnes: A...mentioning
confidence: 99%